EMPAN PAPAN: ETIKA KOMUNIKASI DI MEDIA SOSIAL DALAM PERSPEKTIF BUDAYA JAWA - Shely Cathrin; Reno Wikandaru; Achmad Busrotun Nufus; Sri Sudarsih; Destriana Saraswati (JURNAL LENSA MUTIARA KOMUNIKASI, 2020)
Communication ethics is still a problem in the public domain, especially on social media. There were several viral cases on the internet due to ethical issues in communicating on social media lately. The bias of social media space as private space which is consumed publicly has caused ethical problems in the field of communication. This ethical problem needs to be overcome by educating society about communication ethics in the public sphere, especially on social media. This study aims to describe the concept of empan papan as one of the key concepts in Javanese communication ethics. Based on literature studies combined with hermeneutic analysis, the results show that empan papan can be an alternative communication ethics in the era of information technology. Empan papan is the concept of Javanese situational communication ethics which emphasizes communication on five principles, namely the principle of self-placement, the principle of truth, the principle of accuracy, the principle of situation, and the principle of conditions. This study recommends the need to educate society about the use of communication ethics on board leaders in social media.